Interferensi Morfologi Bahasa Aceh dalam Tulisan Bahasa Indonesia Mahasiswa Universitas Teuku Umar - Siti Jahria Sitompul; Agus Pratama; Al Zuhri; Nurasma Aripin (Pencerah Publishing, 2021)
The Indonesian language has a position and function as the national language and the official language of the country. This led to the need for The Indonesian language to be built and developed as the default language. However, the development of The Indonesian language in accordance with official language rules is often overlooked due to language interference or deviations due to the influence of regional languages that are already inherent in the Indonesian nation. This interference even occurs among students whose ideas and thoughts must be poured through scientific writing in accordance with official linguistic rules. This clearly hinders the smooth communication that should not happen again at the student level. In this study, the researchers found four interferences at the morphological level of all Teuku Umar University students who settled or lived in Alue Bata. The four words consist of three basic words: laot, tepong, and tawe and one-word reduplication (re-word) namely meunasah-meunasah. This should be avoided so that the Indonesian language as the identity of the nation is maintained in accordance with applicable rules.